Approximation methods for discrete lot streaming in flow shops - Chen, Jiang; Steiner, George; McMaster University, Michael G. DeGroote School of Business (My University, 1995)
Lot streaming is the process of splitting a job or lot to allow overlapping between successive operations in a multistage production system. This use of transfer lots usually results in a shorter makespan for the corresponding schedule. In this paper, we present two quickly obtainable approximations of very good quality for the discrete lot streaming problem in flow shops.
12 leaves ; Includes bibliographical references (leaves 10-12). ; "June, 1995." ;
This research was supported in part by the Natural Sciences and Engineering Research Council of Canada under Grant No.OGP0001798.
Keywords: Business; Business; Production scheduling > Mathematical models Economic lot size > Mathematical models Programming (Mathematics) Mathematical optimization